Children's Technology Use during the Pandemic Period - Nihal Dulkadir Yaman; Ramazan Dulkadir; Fatih Yaman (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The COVID-19 pandemic has caused people to stay home all over the world. People started to perform their daily tasks remotely. Due to staying at home, the use of technology increased, and people began to live in a digital environment. This situation has started to cause problems in young people as well as adults. During the pandemic, children experienced social and psychological consequences, including a decrease in social activities, an increased desire to use technological devices, aggression towards their family and surroundings, a decreased desire to play with friends, and becoming quieter and more introverted. In this context, the aim of this study is to determine the usage patterns, reasons, and resulting consequences of children's excessive use of technology during the pandemic. The study was designed based on a survey model. For this purpose, a measurement tool developed by the researchers was used, and data were collected from 132 parents. The participants' educational levels were generally at the undergraduate level (62%). Descriptive statistics (%, f, x̄, sd), Mann Whitney U test and Kruskal Wallis H test were used in the analysis of the data. As a result of the analyses, the most significant finding of the study is that children spent a significant amount of time with technological devices during the pandemic and this had a negative impact on their sleep patterns and physical health. It was determined that there was no significant difference in parents' situations in terms of variables such as gender, educational level and internet use experience. However, there was a significant difference in terms of the number of children they had. It was found that problems related to excessive technology use in children occurred. In this regard, families have certain responsibilities. Parents are primarily responsible for protecting their children from the effects of technology. Training programs can be developed for parents to fulfill these responsibilities and become conscious parents. Parents can direct their children towards physical activities and spend more time with them.